ANALISIS KETIMPANGAN PENDAPATAN KABUPATEN/KOTA DI PROVINSI GORONTALO - Annisa Hidayah (2022)
This research was conducted with the aim of identifying income inquality that is affected by GRDP per capita, Human Development Index, and Total Gross Fixed Capital Formation and Changes in District/City Inventory in Gorontalo Province. This study used six regions in Gorontalo Provnce including Gorontalo Regency, Boalemo Regency, Pohuwato Regency, Bone Bolango Regency, North Gorontalo Regency and Gorontalo City. Determination of sample using saturated sampling technique with six districts/cities in Gorontalo Province in the 2016-2020 period, so that the total sample in this study is 30 research data. Regarding the data worked on in this research is secondary data whose source comes from the Central Bureau of Statistics of Gorontalo Province. In connection with carying out tests that seek to prove the hypothesis in research, the multiple linear regresion method is used with panel data analysis techniques with Eviews 12 software as the testing medium and a significance level of 5%. The partial test results prove that Total Gross Fixed Capital Formation and Inventory Changes have a signifcant effect on income inequality, while GRDP per capita and Human Development Index have no significant effect on income inequality. The test results also interpret that simultaneously GRDP per capita, Human Development Index, and Total Gross Fixed Capital Formation and Inventory Changes have a signficant influence on income inequality.